Between the inside and the outside: The raven between verses and comics - Nascimento, Elisa Prado (Revista de Letras, 2015)
The poem The Raven, by Edgar Allan Poe (1965a), presents the conversation between a man grieving for his beloved Lenore, and a raven which invades his room during a winter night. The speaker’s questions to the bird are always answered with the word “nevermore”, which eventually intensifies his sorrow, as he faces the fact that he will nevermore see his beloved one. Also, he realizes that the crow will never leave his room, as well as his sadness will never leave his heart. According to Poe, the raven symbolizes the speaker’s state of mind. At the same time, his state of mind is a result of the dialogue between him and the raven, i.e., between his intimacy and an outside element which invades your room. The present article aims to investigate this dialectical relationship between the inside and the outside, intimacy and exteriority, in The Raven, as well as in an adaptation of this poem to comics, by Luciano Irrthum (2001). This investigation is based on Bachelard’s considerations presented in The Poetics of Space.